Effect of hydrogen and ethanol addition in cashew nut shell liquid biodiesel operated direct injection (DI) diesel engine. (26th January 2022) - Thanigaivelan, V.; Loganathan, M.; Vikneswaran, M.; Venkatramanan, S.; Manickam, M.
Abstract: In this experimental research, the hydrogen gas at a different flow rate (4 lpm, 8 lpm, & 12 lpm) is introduced into the intake port of a diesel engine fueled with B20 (20% CNSL (Cashew nut shell liquid) + 80% diesel) biodiesel blend to find out the best H2 flow rate. Then, ethanol-blended (5%, 10%, and 15% by volume) B20 blend along with the best H2 flow rate are tested in the same engine to examine the engine performance. The experimental results showed that B20 with 8 lpm H2 flow gives the maximum brake thermal efficiency and subsequently reduces the BSFC. Furthermore, by blending ethanol with the B20 blend, the BTE of the engine is improved further. The 10% ethanol blended B20 blend with 8 lpm hydrogen flow gives the maximum BTE of 37.9% higher than diesel whose values are 33.6% at full load. Also, this fuel combination led to the maximum reduced levels of CO and HC emissions with an increase in exhaust gas temperature and NOx emissions. From the results, the 10% ethanol blended B20 blend with 8 lpm H2 flow dual-fuel configuration is recommended as an alternative to sole diesel fuel. Highlights: 20% thermally cracked cashew nut shell oil blended diesel is tested. Intake air was enriched with H2 gas at 4, 8, and 12 lpm. Biodiesel blend with 8 lpm H2 flow rate increase the BTE by 6.5%. Ethanol blended into biodiesel blend in the ratio of 5:95, 10:90, and 15:85. 10% ethanol blend with 8 lpm H2 gives maximum BTE with least CO and HC emission.